INOVASI LAYANAN BARU DENGAN DESIGN THINKING SEBAGAI UPAYA UNTUK MEMPERTAHANKAN LOYALITAS PELANGGAN BANK TRADISIONAL - Anggita Nurma Haulika; Beni Dwi Komara; Aries Kurniawan (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
Pricewaterhousecooper (PWC) released a report shocking the banking world that "traditional banks cannot survive in 2025". Whether you realize it or not, millennials or Gen Z are currently using financial technology or fintech, which are starting to take on the role of traditional banks. Technological developments, e-commerce, social media and the internet have resulted in quite large and rapid changes. Traditional banks must innovate new services in order to maintain the loyalty of customers or bank customers. This study aims to find out how new service innovations in banks are, this innovation is a response and bank action against competitors in the banking world. This innovation approach is carried out using the design thinking method and the research uses descriptive qualitative. The object of this research involved 6 team members from Bank Jabar Banten Syariah whose process was accompanied by 1 facilitator and 1 Design Thinking expert resource person. The results of this study provide an overview of the innovation process from the empathy, define, idea, prototype to the test process that produces new service innovations at banks. Service innovation "Gold Installment for Study", a service program to help parents with elementary-high school aged children to be consistent in allocating education funds every month through the auto debit feature. Implementation of innovation is carried out online through the zoom application and the help of the miro application in sharing collaborative work boards.